Myocardial revascularization results: electrical, structural, and geometric left ventricular remodelling in diastolic heart failure - I. P. Tatarchenko; N. V. Pozdnyakova; I. A. Petrushin; O. I. Morozova; A. G. Mordovina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To assess the dynamics of structural and geometric left ventricular (LV) remodelling and myocardial electrical instability in patients with post-infarction cardiosclerosis (PICS), at baseline and one year after coronary artery bypass graft (CABG) surgery. Material and methods. The study included 54 patients with PICS (mean age 57,9±6,2 years) and previous coronary revascularization (up to two years earlier). The examination included 12-lead electrocardiography (ECG), with QT interval analysis (QTd, QTс), Holter ECG monitoring, echocardiography, signal-averaged ECG (SA ECG) with late ventricular potential analysis, heart rate variability (HRV) and heart rate turbulence (HRT) assessment. Results. The analysis of structural and geometric parameters in patients after myocardial revascularization demonstrated adaptive LV remodelling, independent of the type of myocardial changes. Improved coronary perfusion after revascularization was associated with positive dynamics of SA ECG parameters, normalization of the last part of filtered QRS complex (in 26 % of the patients), and a decrease in QTd (-24 %) and QTс (-12,8 %). After CABG, HRT and HRV parameters also improved. Conclusion. In patients with coronary heart disease, the parameters of myocardial electrical instability could be used as additional, non-invasive markers of revascularization effectiveness.